2015
DOI: 10.1038/hdy.2015.95
|View full text |Cite
|
Sign up to set email alerts
|

Importance of demographic history for phylogeographic inference on the arctic–alpine plant Phyllodoce caerulea in East Asia

Abstract: Arctic-alpine plants have enormous ranges in the Northern Hemisphere. Phylogeographic studies have provided insights into their glacial survival as well as their postglacial colonization history. However, our understanding of the population dynamics of disjunct alpine populations in temperate regions remains limited. During Pleistocene cold periods, alpine populations of arctic-alpine species in East Asia were either connected to an ice-free Beringia refugium or they persisted with prolonged isolation after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The blue cluster occurs in Beringia and in northern Japan (Figure ), which largely corresponds to the widespread AFLP cluster dominating in Beringia (no Japanese samples were included in the AFLP study of Eidesen et al., ). Recent phylogeographic studies have revealed genetic similarity as well as demographic closeness between northern Japan and Beringia in alpine as well as arctic‐alpine plants (Hata et al., ; Ikeda, Higashi et al., , Ikeda et al., ), suggesting that cold‐adapted species may have spread widely in northern East Asia. Thus, the present distribution of the blue cluster probably reflects an extensive distribution of K .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blue cluster occurs in Beringia and in northern Japan (Figure ), which largely corresponds to the widespread AFLP cluster dominating in Beringia (no Japanese samples were included in the AFLP study of Eidesen et al., ). Recent phylogeographic studies have revealed genetic similarity as well as demographic closeness between northern Japan and Beringia in alpine as well as arctic‐alpine plants (Hata et al., ; Ikeda, Higashi et al., , Ikeda et al., ), suggesting that cold‐adapted species may have spread widely in northern East Asia. Thus, the present distribution of the blue cluster probably reflects an extensive distribution of K .…”
Section: Discussionmentioning
confidence: 99%
“…procumbens may have persisted in central Japan, but their historical relationships to the remaining range remain unclear. Because K. procumbens is diploid (Elven, Murray, Yu, & Yurtsev, ; Shimizu, ), we can use the same approach based on sequencing of multiple nuclear genes as we used in previous studies of diploid Ericaceae species (Ikeda, Yakubov, Barkalov, & Setoguchi, ; Ikeda et al., ; Ikeda, Sakaguchi, Yakubov, Barkalov, & Setoguchi, ). We therefore considered K. procumbens to be appropriate for assessing the temporal framework underlying circumarctic genetic structure.…”
Section: Introductionmentioning
confidence: 99%
“…caerulea that showed statistical evidence for introgression from P . aleutica (Ikeda, Sakaguchi, Yakubov, Barkalov, & Setoguchi, ) were excluded from the analysis. Analysed individuals are indicated in Table S1.1 in Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, without phylogeographical investigation in intermediate populations such as the Kuril Islands, we cannot fully support this scenario. As with previous inferences in the other alpine shrubs Cassiope lycopodioides (Ikeda et al ., ) and Phyllodoce caerulea (Ikeda et al ., ), the connected range between northern Japan and Beringia is a plausible alternative scenario for T. camtschaticum during the last glacial period. In this case, a scenario of range fragmentation following post‐glacial climate warming plausibly resulted in the genetic divergence between Beringia and Japan; however, genetic drift concurring the scenario would not explain the geographically structured pattern of genetic divergence.…”
Section: Discussionmentioning
confidence: 96%
“…These studies indicate that the disjunct ranges of alpine plants are considered to have been connected widely in East Asia during the last glacial period. This biogeographical history is further supported by another alpine shrub Phyllodoce caerulea (Ikeda et al ., ). Accordingly, phylogeographical investigations including Kamchatka and northern Japan could provide insight into the biogeographical history of flora in the Aleutian Islands.…”
Section: Introductionmentioning
confidence: 97%